2002
DOI: 10.1183/09031936.02.00268802
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone propionate attenuates platelet-activating factor-induced gas exchange defects in mild asthma

Abstract: Inhaled glucocorticosteroids may reduce airway mucosal oedema in acute asthma. Inhaled platelet-activating factor (PAF) provokes pulmonary gas exchange disturbances, similar to those shown in severe asthma, which may be due to increased airway plasma leakage.This randomized, double-blind, placebo-controlled, crossover study investigated the effects of high doses of inhaled fluticasone propionate (FP) in 12 patients with mild asthma before and after PAF inhalation. Patients were studied before and 12 h after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
(61 reference statements)
1
11
0
1
Order By: Relevance
“…Anthropometric and functional data were within normal limits and close to those reported in previous studies [15]. There were no differences between the placebo and the formoterol subjects (table 2 and fig.…”
Section: Baseline Findings (Before Platelet-activating Factor)supporting
confidence: 67%
See 1 more Smart Citation
“…Anthropometric and functional data were within normal limits and close to those reported in previous studies [15]. There were no differences between the placebo and the formoterol subjects (table 2 and fig.…”
Section: Baseline Findings (Before Platelet-activating Factor)supporting
confidence: 67%
“…In contrast, formoterol was unable to modulate either facial flushing or neutrophil kinetics. Based on previous work by the authors in both normal subjects [3,8,9] and mild asthmatics [4,10,15], the authors postulate that PAF-induced pulmonary gas exchange defects and increases of Rrs are related to airway narrowing secondary to abnormally increased microvascular leakage, rather than to a primary constrictor effect on airway smooth muscle. SABAs were among the first agents to exhibit anti-oedema effects by preventing separation of endothelial cells at postcapillary venular sites [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that activation of the PAF-receptor-mediated signaling pathway may be one mechanism by which (S) -albuterol induces HBSMC proliferation. PAF is an endogenous lipid mediator with mitogenic properties [40, 41], and has been reported to aggravate asthmatic conditions [42,43,44,45]. In our study, the specific PAF receptor antagonist CV-3988, at a low concentration of 1 µ M , inhibited (S) -albuterol-induced cell growth, but neither reversed levalbuterol-induced inhibition of cell growth, nor produced additive inhibition with levalbuterol.…”
Section: Discussionmentioning
confidence: 64%
“…However, fewer clinical studies have addressed a possible effect of ICS on the pulmonary circulation. In asthmatics, inhalation of platelet aggregation factor (PAF) has been used for acute induction of a perfusion-ventilation mismatch in asthmatics [19]. Within 45 minutes after inhalation of fluticasone propionate, the corticosteroid ameliorated the PAF induced gas exchange mismatch, measured as improved systemic arterial oxygen tension.…”
Section: Discussionmentioning
confidence: 99%